Inflammatory role of extracellular sphingolipids in Cystic Fibrosis. (November 2019) - Zulueta, Aida; Peli, Valeria; Dei Cas, Michele; Colombo, Michela; Paroni, Rita; Falleni, Monica; Baisi, Alessandro; Bollati, Valentina; Chiaramonte, Raffaella; Del Favero, Elena; Ghidoni, Riccardo; Caretti, Anna
Highlights: Cystic Fibrosis mesenchymal stem cells exhibit an enhanced sphingolipid metabolism. CFTR dysfunction associates with release of EV enriched in inflammatory ceramides. Extracellular lipids play a critical role in Cystic Fibrosis inflammation. Abstract: Ceramide is emerging as one of the players of inflammation in lung diseases. However, data on its inflammatory role in Cystic Fibrosis (CF) as part of the extracellular machinery driven by lung mesenchymal stem cells (MSCs)-derived extracellular vesicles (EVs) are missing. We obtained an in vitro model of CF-MSC by treating control human lung MSCs with a specific CFTR inhibitor. We characterized EVs populations derived from MSCs (ctr EVs) and CF-MSCs (CF-EVs) and analyzed their sphingolipid profile by LC–MS/MS. To evaluate their immunomodulatory function, we treated an in vitro human model of CF, with both EVs populations. Our data show that the two EVs populations differ for the average size, amount, and rate of uptake. CF-EVs display higher ceramide and dihydroceramide accumulation as compared to control EVs, suggesting the involvement of the de novo biosynthesis pathway in the parental CF-MSCs. Higher sphingomyelinase activity in CF-MSCs, driven by inflammation-induced ceramide accumulation, sustains the exocytosis of vesicles that export new formed pro-inflammatory ceramide. Our results suggest that CFTR dysfunction associates with an enhanced sphingolipid metabolism leading to the release of EVs that export the excess of pro-inflammatory Cer to the recipient cells, thus contributing to maintain the unresolved inflammatory status of CF.